Fish Waste MSMEs Empowerment Program in Kalanganyar Village, Sedati District, Sidoarjo Regency Through Village Driven Development Approach - Kristianto Kristianto; Cyntya Sri Zuwanita (Ridwan Institute, 2022)
Aquatic resources and marine products are the most significant economic potential in Kalanganyar Village. Therefore, development in this sector, such as local economic development with MSMEs, must be a severe concern for the government and related parties. This paper aims to discusses the empowerment program carried out by Pertamina DPPU Juanda in developing MSMEs in Kalanganyar Village which is carried out using the participatory rural appraisal (PRA) method based on the Village-Driven Development approach. As a result, the community empowerment program created two innovative products and active involvement of each interest group. In addition, community empowerment, which is carried out with a village-driven development approach, can strengthen the position of the village government as a more democratic actor in development and essential services for the community.